Penggunaan Mobile Banking di Denpasar Bali: Perspektif Digital Divide - Budiutama, I Komang Arya Sindura; Giri, Refi Rifaldi Windya (Ekonomis: Journal of Economics and Business, 2024)
The development of digital technology in the era of Industry 4.0 has facilitated societal activities. The internet penetration rate in Indonesia has reached 72.02 percent, indicating high internet access. The innovation of mobile banking by Bank Indonesia has helped simplify transactions, although the value of mobile banking transactions is still lower compared to conventional banks. In Bali, a region with rapid economic growth and high internet access, coupled with the increasing use of e-money, however, the level of digital literacy in Bali is still low, with a score of 47.48, which needs to be improved. The use of mobile banking needs to be balanced with efforts to bridge the digital divide. The research utilizes a quantitative method with data analysis techniques using PLS-SEM through WarpPLS 7.0 software. Nonprobability purposive sampling is used as the sampling technique. Data collection involves primary and secondary data through the distribution of questionnaires. The sample size in this research is 302 respondents from the population of mobile banking users in Denpasar. The findings indicate that motivation, physical and material access, mobile banking skills, and usage significantly and positively influence the use of mobile banking in Denpasar.